Pelaksanaan Lelang Terhadap Penerapan Prinsip Keadilan Di Indonesia - Ria Juliana Siregar (LPPM Universitas HKBP Nommensen, 2022)
Auction is the process of buying and selling goods or services by offering to bidders, bidding a higher price, and then selling the item to the highest bidder. In economic theory, auction refers to several trading mechanisms or regulations from the capital market. If we look at it from a legal perspective, auctions are legal institutions that always exist in the legal system in Indonesia to meet the needs of the community, one of which is to fulfill the sale of an object through auction as stipulated in laws and regulations. This research is a qualitative research in which the aim is to understand phenomena in a natural social context by prioritizing the process of in-depth communication interaction between the researcher and the phenomenon being studied. By using this type of research, researchers directly go into the field looking for information relating to the auction mechanism of goods against the principle of justice in Indonesia. Justice in Indonesia is a legal umbrella for all people. The importance of justice is that it does not balance with existing legal regulations.